Uncovering the Digital Divide: Gender-based Insights into Students’ Technology and Media Literacy in Mathematics Learning - Herlina, Sari; Julianti, Dola; Zamsuri, Ahmad (Edumatica : Jurnal Pendidikan Matematika, 2025)
The development of digital technology is increasingly sophisticated. The need for the existence of technology is not only in everyday life but also needed in learning mathematics. This article examines how Technology Literacy and Student Media Literacy in Mathematics Learning. The urgency of this research lies in achieving equality and inclusivity in digital education. This research is survey research. The number of samples is 165 students. Male students who filled out the questionnaire were 45.7% while female students were 54.3%. The age range of those who completed the questionnaire was 17-24 years. The data collecting approach was carried out utilizing a questionnaire using Google Form to reach many research participants. Descriptive analysis was used to analyse the data. The results showed that the average student technology literacy was 61.84% in the fairly good category, while the average student media technology was 54,46% in the pretty good category. The results of the analysis based on gender, it was found that female's technology literacy and media literacy were higher than males. Further research is urgently needed to develop learning strategies that bridge the gender-based digital divide and promote equal access and technological literacy in mathematics learning.